Addressing Community Needs During the Hurricane Response and Recovery Efforts Through Community Assessments for Public Health Emergency Response (CASPER)—United States Virgin Islands, 2017-2018. (7th March 2019) - Schnall, Amy Helene; Roth, Joseph (Jay); Ellis, Brett; Seger, Krystal; Davis, Michelle; Ellis, Esther M.
ABSTRACT: Objectives: Two category 5 storms hit the US Virgin Islands (USVI) within 13 days of each other in September 2017. This caused an almost complete loss of power and devastated critical infrastructure such as the hospitals and airports Methods: The USVI Department of Health conducted 2 response Community Assessments for Public Health Emergency Response (CASPERs) in November 2017 and a recovery CASPER in February 2018. CASPER is a 2-stage cluster sampling method designed to provide household-based information about a community's needs in a timely, inexpensive, and representative manner. Results: Almost 70% of homes were damaged or destroyed, 81.2% of homes still needed repair, and 10.4% of respondents felt their home was unsafe to live in approximately 5 months after the storms. Eighteen percent of individual respondents indicated that their mental health was "not good" for 14 or more days in the past month, a significant increase from 2016. Conclusion: The CASPERs helped characterize the status and needs of residents after the devastating hurricanes and illustrate the evolving needs of the community and the progression of the recovery process. CASPER findings were shared with response and recovery partners to promote data-driven recovery efforts, improve the efficiency of the current response and recovery efforts, and strengthen emergency preparedness in USVI. ( Disaster Med Public Health Preparedness. 2019;13:53-62)